2010
DOI: 10.2353/ajpath.2010.100369
|View full text |Cite
|
Sign up to set email alerts
|

Nf1−/− Schwann Cell-Conditioned Medium Modulates Mast Cell Degranulation by c-Kit-Mediated Hyperactivation of Phosphatidylinositol 3-Kinase

Abstract: Neurofibromatosis type 1 (NF1) is a common genetic disorder and is characterized by both malignant and nonmalignant neurofibromas, which are composed of Schwann cells, degranulating mast cells, fibroblasts, and extracellular matrix. We and others have previously shown that hyperactivation of the c-Kit pathway in an Nf1 haploinsufficient microenvironment is required for both tumor formation and progression. Mast cells play a key role in both tumorigenesis and neoangiogenesis via the production of matrix metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 34 publications
2
24
0
8
Order By: Relevance
“…Specifically, a Rac2-Pak1-p38 signaling pathway induces F-actin rearrangement and cell motility, although the precise downstream effectors remain unknown (136). These cytoskeletal observations directly correlate with a genetic study showing that Nf1 +/- mast cells require PI-3K activity for Nf1 -/- Schwann cell conditioned media-dependent degranulation (140). Moreover, SCF-induced PI-3K-Rac2 activity promotes Akt's modulation of Bcl-2 family proteins (e.g.…”
Section: Schwann Cells Nf1 Haploinsufficient Mast Cells and The Tumsupporting
confidence: 78%
See 1 more Smart Citation
“…Specifically, a Rac2-Pak1-p38 signaling pathway induces F-actin rearrangement and cell motility, although the precise downstream effectors remain unknown (136). These cytoskeletal observations directly correlate with a genetic study showing that Nf1 +/- mast cells require PI-3K activity for Nf1 -/- Schwann cell conditioned media-dependent degranulation (140). Moreover, SCF-induced PI-3K-Rac2 activity promotes Akt's modulation of Bcl-2 family proteins (e.g.…”
Section: Schwann Cells Nf1 Haploinsufficient Mast Cells and The Tumsupporting
confidence: 78%
“…(130, 135, 136, 138-140). However, biochemical investigations have additionally shown that the PI-3K-dependent pathway reinforces the classical Raf-Mek-Erk cascade through the activity of the p21 activated kinases (Paks) (130, 136).…”
Section: Schwann Cells Nf1 Haploinsufficient Mast Cells and The Tummentioning
confidence: 99%
“…This cell-to-cell interaction is mediated through the cell surface cytokine receptor known as c-kit. [9][10][11] Schwann cells in patients with NF1 express higher levels of c-kit compared with normal Schwann cells. 12 It is known that more mast cells are recruited and activated in plexiform than in encapsulated neurofibromas, but that increased mast cell signaling is seen in both NF1 tumor types.…”
Section: Figurementioning
confidence: 94%
“…Using a combination of bone marrow transplantation and pharmacological inhibitor approaches, mast cells are required for murine plexiform neurofibroma formation and continued growth [47]. In these experiments, mast cells recruited by Nf1- deficient Schwann cell-produced stem cell factor (SCF or KIT-ligand) secrete cytokines that increase neurofibroma growth [48]. Moreover, SCF can also stimulate Nf1 +/− mast cells to increase fibroblast proliferation and collagen deposition, thereby forming a permissive tumor microenvironment [49].…”
Section: Tissue Levelmentioning
confidence: 99%